Alternative education in Palestinian-Arab society in Israel: Rationale and characteristics. (May 2019) - Magadley, Wissam; Amara, Muhammad; Jabareen, Yousef
Highlights: Non-authoritarian and informal teacher-student relationships are key characteristics of alternative education schools. The schools connect students to Palestinian-Arab history and culture to help them form a sense of identity and belonging. The schools place emphasis on non-traditional subject matters such as, art, music, drama and dance. Committed and motivated teachers are key to preserving the alternative character of the schools. Abstract: The past two decades have witnessed the emergence of alternative schools in Palestinian-Arab society in Israel. Drawing on data from interviews and observations at two prominent alternative schools, we examine the rationale for establishing alternative schools in Palestinian-Arab society in Israel and their characteristics. The analysis reveals that discontent with the state-mandated curriculum, the lack of autonomy, and the excessive focus on academic achievement in mainstream schools were the main reasons for establishing alternative schools. The analysis identified six major themes that distinguish these schools from mainstream schools: interpersonal relationships; alternative teaching practices; alternative subjects and extracurricular activities; strengthening students' sense of Palestinian national and cultural identity; active parental engagement; and committed, motivated teachers. The findings are discussed in relation to mainstream schools in Palestinian-Arab society in Israel.